2011
DOI: 10.1016/j.explore.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Stress Reduction Versus Pharmacotherapy for Chronic Primary Insomnia: A Randomized Controlled Clinical Trial

Abstract: Objective To investigate the potential of Mindfulness-Based Stress Reduction (MBSR) as a treatment for chronic primary insomnia. Design Randomized controlled trial. Setting University health center. Patients 30 adults with primary chronic insomnia based on DSM-IV-TR criteria were randomized 2:1 to MBSR or pharmacotherapy (PCT). Interventions MBSR, a program of mindfulness meditation training consisting of 8 weekly 2.5 hour classes and a day-long retreat, with ongoing home meditation practice expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
195
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(214 citation statements)
references
References 43 publications
13
195
1
3
Order By: Relevance
“…For example, participants selected for the interventions were characterized by longer SOL, but not lower TST, compared with those not selected for the interventions. These results are also consistent with emerging empirical evidence showing that children and adolescents with anxious and depressive symptoms have particular difficulties with wakefulness in bed (Lovato & Gradisar, 2014), especially sleep initiation (Alfano et al, 2013;Forbes et al, 2008), and with the results of other sleep interventions that have found SOL among the most improved variables (Bei et al, 2013;Bootzin & Stevens, 2005;Clarke et al, 2015;de Bruin et al, 2015de Bruin et al, , 2014Garland et al, 2014;Gradisar, Dohnt, et al, 2011;Gross et al, 2011;Koffel et al, 2015;Schlarb et al, 2011;Trauer et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…For example, participants selected for the interventions were characterized by longer SOL, but not lower TST, compared with those not selected for the interventions. These results are also consistent with emerging empirical evidence showing that children and adolescents with anxious and depressive symptoms have particular difficulties with wakefulness in bed (Lovato & Gradisar, 2014), especially sleep initiation (Alfano et al, 2013;Forbes et al, 2008), and with the results of other sleep interventions that have found SOL among the most improved variables (Bei et al, 2013;Bootzin & Stevens, 2005;Clarke et al, 2015;de Bruin et al, 2015de Bruin et al, , 2014Garland et al, 2014;Gradisar, Dohnt, et al, 2011;Gross et al, 2011;Koffel et al, 2015;Schlarb et al, 2011;Trauer et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…For example, despite popularized claims of the therapeutic benefit for meditation for sleep, data from randomized trials evaluating mindfulness meditation for sleep disturbances are mixed. [28][29][30][31][32][33] Conversely, three recent randomized controlled studies evaluating the benefit of Tai Chi for sleep have demonstrated improvement in subjective sleep parameters (i.e., Pittsburgh Sleep Quality Index [PSQI]). [14][15][16] However, larger randomized controlled trials with objective outcome measures are needed to improve our understanding of the efficacy of alternative mind-body therapies, with particular attention given to important methodological issues that are related to behavioral interventions, such as difficulty with blinding.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their influence on the subjective well-being, mindfulness-based interventions have shown great efficacy for different types of mental disorders and chronic diseases, including chronic pain (Morone, Lynch, Greco, Tindle, & Weiner, 2008) and primary insomnia (Gross et al, 2011). They have also proved effective in improving the quality of life of cancer patients (Carlson, Speca, Patel, & Goodey, 2004), reducing anxiety in patients with heart conditions (Tácon, McComb, Caldera, & Randolph, 2003), and reducing mood disorders (Williams, 2008).…”
mentioning
confidence: 99%